Pertumbuhan dan Hasil Kandungan Fe dan Zn pada Beras dari Kultivar Padi Ladang di Kabupaten Timor Tengah Utara - Asep Ikhsan Gumelar; Florian Mayesti Prima R. Makin; Deseriana Bria (Paspalum: Jurnal Ilmiah Pertanian, 2023)
Field rice (paddy field) is one of the important crops/commodities and is an integral part of the dry land farming system in North Central Timor district. The content of rice is to meet the needs of carbohydrates in the body. The materials used are harvested grain from the local North Central Timor rice cultivar which has been carried out for the 2022 planting season. A total of 6 field rice in North Central Timor district were to be tested for Fe and Zn content. Grain samples were taken from crops grown in the same season and location, namely in the dry season of 2022. This study aims to identify local Timorese rice varieties that have high and stable Fe and Zn contents. The study was conducted in the Field Laboratory of the Faculty of Agriculture, University of Timor with a non-factorial Randomized Block Design consisting of 6 cultivar treatments V1 V2 V3 V4 V5 and V6 and the XRF Laboratory, BB Padi Sukamandi. Test the content of Fe and Zn using an XRF machine with an x-ray based performance system. A total of 6 types of field rice were tested for the content of Fe and Zn in brown and polished rice and repeated in duplicate. The content of Fe and Zn is expressed in units of ppm. Data processing was carried out using Excel and SAS 9 software. The results showed that there were differences in the growth and production components between the local Timor and East Timor upland rice cultivars. Cultivars with cultivar V2 (muit fua naek) productivity as seen from the t/ha yield of 3.20 tons per ha were significantly higher than the other cultivars. The results of the analysis of Fe and Zn content showed that cultivar V6 (Aen Mael) had the highest Fe content of 15.1 among the other cultivars, and the lowest was cultivar V4 (Aen Ek ELo) which had an Fe content of 13.0. The highest Zn content was in cultivar V5 (Aen Muit Fua Ana) with a Zn content of 27.9 while the lowest was in cultivar V2 (Muit Fua Naek) with a Zn content of 20.4.